Eksistensi Manajemen Pendidikan Islam dalam Tatanan Pendidikan Indonesia di Masa Depan - Halimatun Syakdiah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The objective of this study is to describe the concept of Islamic education management in the future Indonesian education system, to define the management of Muslim education in Indonesia's future educational system, and to implement Islamic educational management in Indonesia’s future education system. This research uses descriptive qualitative research methods with a library survey approach, i.e. research supported by literature related to research issues. The results of the research show that the concept and urgency of Islamic education management in the Indonesian education system in the future is already appropriate management is placed in an urgent position in the system of education especially Islamic Education itself. As the religion that regulates all the actions of the people, Islam always provides important information about how to conduct management so that all activities in the world of education can go as they should and produce individuals who are called humans. Therefore, in implementing educational management as a process of applying the theory and principles of management so that activities in educational institutions can run effectively in order to the objectives of education itself, in relation to its application, Islamic education management must get full support of existing resources to benefit the realization of the performance of educational organization that produces reliable, professional and spiritually firm graduates. Finally, the management of Islamic education no longer loses its function in humanizing human beings because of the Islamic management of education as an essential way of managing educational institutions that implants personality based on earthly and ukhravi values in each individual. The results of this research are expected to contribute to addressing the issue of Islamic education so that it can develop itself and enhance its existence in the building of the Indonesian nation.